Successful EUS-guided antegrade stenting for malignant severe biliary obstruction combined with a newly developed plastic stent - Minami, Kazuhiro; Iwasaki, Eisuke; Itoi, Takao; Fukuhara, Seiichiro; Horibe, Masayasu; Seino, Takashi; Kawasaki, Shintaro; Katayama, Tadashi; Takimoto, Yoichi; Tamagawa, Hiroki; Machida, Yujiro; Hamamoto, Yasuo; Ogata, Haruhiko; Kanai, Takanori (Endoscopy International Open, 2018)
Background and study aims We report the effectiveness of a newly developed plastic stent for preventing bile leakage after endoscopic ultrasonography (EUS)-guided antegrade stenting. This treatment was performed on a 59-year-old woman with malignant obstructive jaundice caused by peritoneal metastasis. First, we attempted transpapillary drainage using short-type single-balloon enteroscopy-assisted endoscopic retrograde cholangiopancreatography, but we could not achieve it. We then attempted EUS-guided antegrade stenting through the intrahepatic bile duct from the esophagojejunal anastomosis. We successfully inserted uncovered metallic stents for common bile duct and a newly plastic stent for hepaticojejunostomy from the antegrade approach. There were no adverse events after the treatment.